Thigh sarcopenia and hypoalbuminemia predict impaired overall survival after infrainguinal revascularization in patients with critical limb ischemia. (October 2020) - Morisaki, Koichi; Furuyama, Tadashi; Matsubara, Yutaka; Inoue, Kentaro; Kurose, Shun; Yoshino, Shinichiro; Nakayama, Ken; Yamashita, Sho; Yoshiya, Keiji; Mori, Masaki
Objective: This study was performed to determine whether thigh sarcopenia can serve as a clinically relevant predictor of postoperative complications and overall survival after revascularization in patients with critical limb ischemia. Methods: Patients who underwent preoperative computed tomography followed by infrainguinal revascularization from 2006 to 2015 were retrospectively analyzed. An axial computed tomography image was obtained at the midpoint of a line extending from the superior border of the patella to the greater trochanter of the femur. The thigh muscle area and bone area were measured. Thigh sarcopenia was defined as thigh muscle area/thigh bone area of <9. Results: We included 117 patients with critical limb ischemia who underwent infrainguinal revascularization. The overall survival rates at two years were 86.5% and 55.1% in the thigh sarcopenia (−) and (+) groups, respectively ( p  < 0.01). The multivariate analysis showed that thigh sarcopenia (hazard ratio, 2.64; 95% confidence interval, 1.11–6.70; p  = 0.03), cerebrovascular disease (hazard ratio, 3.18; 95% confidence interval, 1.31–7.36; p  = 0.01), and serum albumin level (1 g/dL per increments) (hazard ratio, 0.41; 95% confidence interval, 0.21–0.81; p  = 0.01) were the risk factors for overall survival two years after revascularization. Conclusion: Thigh sarcopenia is a risk factor for two-year overall survival in patients with critical limb ischemia after infrainguinal revascularization.